Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
a) (+) × (?) = (+)
(?) = (+)
b) (-) × (+) = ?
? = (-)
c) (?) × (-) = ?
? is undefined
Step-by-step explanation:
a) (+) × (?) = (+)
From the given equation in the question, by dividing both side of the equation by (+), we have;
((+) × (?))/(+) = (+)/(+)
(?) = (+)/(+) = (+)
Therefore, we have;
(+) × (+) = (+)
(?) = (+)
b) (-) × (+) = ?
From the given equation in the question we apply the operation rules as follows;
(-) × (-) = (+)
(-) × (+) = (-)
Therefore;
(-) × (+) = ? = (-)
? = (-)
c) (?) × (-) = ?
From the rules of multiplication, we have;
(-) × (-) = (+)
(+) × (-) = (-)
Therefore, when (?) = (-), ? = +, from which we have;
(?) ≠ ?, which is an error
Similarly, when (?) = (+), ? = -, therefore, (?) and ?, always changes sign
Therefore, the equation, (?) × (-) = ?, is undefined.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.